2015
DOI: 10.1038/srep14554
|View full text |Cite
|
Sign up to set email alerts
|

Local bacteria affect the efficacy of chemotherapeutic drugs

Abstract: In this study, the potential effects of bacteria on the efficacy of frequently used chemotherapies was examined. Bacteria and cancer cell lines were examined in vitro and in vivo for changes in the efficacy of cancer cell killing mediated by chemotherapeutic agents. Of 30 drugs examined in vitro, the efficacy of 10 was found to be significantly inhibited by certain bacteria, while the same bacteria improved the efficacy of six others. HPLC and mass spectrometry analyses of sample drugs (gemcitabine, fludarabin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
203
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 219 publications
(221 citation statements)
references
References 52 publications
4
203
0
1
Order By: Relevance
“…This experiment revealed that conditioned medium from M. hyorhinis -infected HDFs metabolizes gemcitabine into its deaminated inactive metabolite 2′,2′-difluorodeoxyuridine (7) as has been previously reported (8, 9) (Fig. 1C and fig.…”
supporting
confidence: 82%
“…This experiment revealed that conditioned medium from M. hyorhinis -infected HDFs metabolizes gemcitabine into its deaminated inactive metabolite 2′,2′-difluorodeoxyuridine (7) as has been previously reported (8, 9) (Fig. 1C and fig.…”
supporting
confidence: 82%
“…A recent survey of in situ bacterial effects on frequently used chemotherapeutics suggests profound influence of distinct bacteria speciesonthe antitumor effect of these drugs. 117 Lehouritis et al found that after preincubation with nonpathogenic gram-negative E. coli Nissle 1917 or gram-positive Listeria welshimeri Serovar 6B SLCC5334, 10 of 30 chemotherapeutic drugs (eg, gemcitabine, cladribine, daunorubicin, and so forth) showed reduced cancer cell killing efficacy, whereas 6 drugs (eg, fludarabine phosphate, CB1954, and so forth) showed increased cancer cell killing efficacy in vitro. 117 High-performance liquid chromatography–mass spectrometry studies showed that these effects are often bacteria specific, likely because of the unique biotransforming activities associated with each bacterial species/strain.…”
Section: Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%
“…117 Lehouritis et al found that after preincubation with nonpathogenic gram-negative E. coli Nissle 1917 or gram-positive Listeria welshimeri Serovar 6B SLCC5334, 10 of 30 chemotherapeutic drugs (eg, gemcitabine, cladribine, daunorubicin, and so forth) showed reduced cancer cell killing efficacy, whereas 6 drugs (eg, fludarabine phosphate, CB1954, and so forth) showed increased cancer cell killing efficacy in vitro. 117 High-performance liquid chromatography–mass spectrometry studies showed that these effects are often bacteria specific, likely because of the unique biotransforming activities associated with each bacterial species/strain. 117 The in vitro bacteria-specific effect on drug cytotoxicity can be replicated in vivo using a xenograft mouse tumor (CT26 colon carcinoma) model.…”
Section: Microbiota and Cancer Therapy Efficacymentioning
confidence: 99%
See 2 more Smart Citations